Does exposure to markets promote investment behavior? Evidence from rural Ethiopia - Halefom Nigus; Eleonora Nillesen; Pierre Mohnen (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2023)
This study investigates the effect of exposure to markets on farm households' agricultural investment decisions. We assess whether and how market experience affects farmers' adoption of risky but profitable technologies and explore the role of plausible demand-side barriers therein. Specifically, we hypothesize that risk preferences and locus of control change with market experience and as such may explain the relationship between market experience and investment decisions. We use surveys and incentivized experimental data, collected from the Tigray regional state of Ethiopia and use an Endogenous Switching Probit and IV-Probit models to attenuate endogeneity issues. Our findings suggest, first, that market exposure induces farmers to adopt agricultural technologies, such as chemical fertilizer, improved seeds, manure, and row planting and second, that market experience attenuates risk aversion and, although less robustly so, leads to a more internal locus of control. Policies to in crease farmers' investments may thus not be confined to providing access to technologies and information but should perhaps be complemented with interventions that attend to lowering psychological barriers.
Keywords: C93; G22; H41; O17; 330; Agricultural investment; locus of control; markets; risk preference; Ethiopia